2019
DOI: 10.1590/0103-8478cr20180651
|View full text |Cite
|
Sign up to set email alerts
|

Rural tourism marketing: Lavender tourism in Turkey

Abstract: This study aimed to comprehend rural tourism marketing through the visitors' eyes and discuss its sustainability. What makes rural tourism marketing more sophisticated and complex is that it is a service marketing, associated with agricultural activities, natural conditions and rural areas, and the main providers have no experience in rural tourism or service marketing. The study investigated perception of visitors in a small village, Kuyucak, in the Southwest part of Turkey, where rural tourism based on laven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…Giray et al [ 14 ] investigated the perceptions of tourists in a small village called Kuyucak in southwestern Turkey, where rural tourism based on lavender production has recently developed. Results of an analysis of 175 questionnaires completed by online visitors showed that more than half of the respondents learned about the village through social media.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Giray et al [ 14 ] investigated the perceptions of tourists in a small village called Kuyucak in southwestern Turkey, where rural tourism based on lavender production has recently developed. Results of an analysis of 175 questionnaires completed by online visitors showed that more than half of the respondents learned about the village through social media.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As the review indicates that sustainability is critical for the development of a successful tourism destination, this study included sustainable management as one of the sub-dimensions of tourism destination competitiveness. Substantial evidence suggests that tourism destination marketing is an important and necessary tool for the development of tourism destinations in order to achieve sustainable tourism development (Giray et al, 2019;Matthias and Birgit, 2019). Destination marketing efforts are defined as a continuous process of identifying tourist needs and developing a marketing strategy to meet those needs through enhancement of the travel experience (Manhas, Manrai and Manrai, 2016) Indeed, destination marketing has been demonstrated to be a critical initiative in promoting local resources, acting as an attractor that influences tourists' destination selection decisions (Peceny et al, 2019).…”
Section: Rural Tourism Destination Competitivenessmentioning
confidence: 99%
“…Prior to COVID-19 pandemic, tourism destination marketing is considered as one of the most powerful tools for the development of tourism destinations to achieve sustainable tourism development [24,25]. To enhance tourist's travel experience, tourism destination marketing efforts is a much-needed component, as it is defined as a continuous process to identify the needs of the tourists, developing a marketing strategy to satisfy those needs [26].…”
Section: Rural Tourism Destination Marketing Effortsmentioning
confidence: 99%
“…In sum, Blain [35] suggested that a tourism destination which creates differentiation and gains competitive advantage, as well as practices destination marketing efforts for tourism development, would be an added advantage [36]. Most importantly, rural tourism marketing should work along with the objective of achieving rural economic, social, and environmental advantage [24]. Hence, at the recovery phase of the tourism industry, particularly post-COVID-19, it is predicted that destination marketing efforts will be a much-needed tool for tourism branding and promotion as most of the tourism players are encouraged to venture into digital marketing platforms.…”
Section: Rural Tourism Destination Marketing Effortsmentioning
confidence: 99%